1987
DOI: 10.1038/325683a0
|View full text |Cite
|
Sign up to set email alerts
|

A T-cell receptor γ/CD3 complex found on cloned functional lymphocytes

Abstract: Cloned blood lymphocytes that do not express the alpha- and beta-chains of the T-cell receptor show MHC-unrestricted cytotoxicity. These cells carry the gamma-protein, disulphide-linked either to another molecule or to itself, and associated with the CD3 complex. These observations may help to solve the mystery posed by the discovery of the gamma gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
169
1
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(184 citation statements)
references
References 53 publications
13
169
1
1
Order By: Relevance
“…It is now established that T lymphocytes of this subset express a TCR-y/S (35)(36)(37)(38) and are capable of performing nonrestricted (39,40) as well as MHC-linked specific cytolytic functions (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…It is now established that T lymphocytes of this subset express a TCR-y/S (35)(36)(37)(38) and are capable of performing nonrestricted (39,40) as well as MHC-linked specific cytolytic functions (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…CD4 or CD8 cells are characterized by their expression of the ab form of the T cell receptor whereas a minor subset (< 5% in normal human donors) bears the gd T cell receptor and is CD4 -and CD8 -but CD3 + [82,83]. This subset is markedly expanded during the first phase of TB infection in the mouse [84] and has been suggested to be involved as a first line of defence recognizing heat shock antigens [85], a 10-14 kDa antigen released from the bacilli by heat treatment [86], or low mass non-peptidic ligands on the surface of the macrophage [87].…”
Section: Host Responses and Antigens Involved In Protective Immunity mentioning
confidence: 99%
“…In spite of these extensive investigations, tbe functions of CD4-CD8-TCRa/?+ T cells which have been reported so far are controversial. Borst et al (1987) derived a double-negative TCRa/i+ T cell clone from the peripheral blood of a healthy adult, but this elone had little cytolytic activity. In contrast, Groh et al (1989) first reported the spontaneous MHC-unrestrieted cytotoxic activity of human double-negative TCRa)5+ T eells derived from the skin.…”
Section: Discussionmentioning
confidence: 99%